Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.jprot.2013.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of human dental cementum and alveolar bone

Abstract: Dental cementum (DC) is a bone-like tissue covering the tooth root and responsible for attaching the tooth to the alveolar bone (AB) via the periodontal ligament (PDL). Studies have unsuccessfully tried to identify factors specific to DC versus AB, in an effort to better understand DC development and regeneration. The present study aimed to use matched human DC and AB samples (n=7) to generate their proteomes for comparative analysis. Bone samples were harvested from tooth extraction sites, whereas DC samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 62 publications
(76 reference statements)
3
97
0
1
Order By: Relevance
“…The mineralized portion of the ECM is composed largely of calcium-phosphate in the form of hydroxyapatite plus an extensive type I collagen-rich organic ECM. In addition to collagen, proteomic analysis of decalcified bone suggests that well-over 100 ECM proteins are present in bone (Jiang et al, 2007;Salmon et al, 2013). Similarly, analysis of osteoblasts show that ECM proteins represent 30% of the 315 proteins identified via secretome analysis .…”
Section: Q4mentioning
confidence: 99%
See 1 more Smart Citation
“…The mineralized portion of the ECM is composed largely of calcium-phosphate in the form of hydroxyapatite plus an extensive type I collagen-rich organic ECM. In addition to collagen, proteomic analysis of decalcified bone suggests that well-over 100 ECM proteins are present in bone (Jiang et al, 2007;Salmon et al, 2013). Similarly, analysis of osteoblasts show that ECM proteins represent 30% of the 315 proteins identified via secretome analysis .…”
Section: Q4mentioning
confidence: 99%
“…1 illustrates the simplified cellular anatomy of bone and illustrates that different tissue compartments are connected functionally and spatially. In addition to mineralized bone ECM other unique tissue types exist in association with bone, including, (Jiang et al, 2007) marrow; (Salmon et al, 2013) endosteum; periosteum; and (Bos et al, 2004) the osteocyte perilucanar matrix. Marrow, endosteum, periosteum, and perilucanar matrix are all non-mineralized and contain ECM networks that can regulate the processes of osteoclast development and function, osteoblast progenitor proliferation and differentiation, and osteocyte function.…”
Section: Overview Of Bone Ecm Compartmentsmentioning
confidence: 99%
“…At the proteomic level (Salmon et al 2013), studies of human dental cementum compared with alveolar bone revealed that up to 318 proteins in common can be found in both tissues. Nevertheless, 83 proteins were found exclusively in the cementum, implicated in different cellular pathways.…”
Section: Reparative Capabilities Of Mineralized Tissue: Role Of Cementummentioning
confidence: 99%
“…This SOD is a member of the SOD family that acts as a critical cellular protection against O2− and peroxynitrite. Interestingly, SOD3 was immunolocalized in cervical root cementoblasts and around apical third cementocytes (Salmon et al 2013). These regions are well known as areas sensitive to root resorption; hence, regarding SOD3 localization and its function, this protein could play a key role as a "defense" from oxidative stress during cementum maintenance.…”
Section: Reparative Capabilities Of Mineralized Tissue: Role Of Cementummentioning
confidence: 99%
“…2,3 It may also have many extraskeletal effects by regulating a large number of genes. The concentration of ionized calcium in extracellular and intracellular compartments is very tightly regulated in vertebrates as well as in invertebrates, whereas an endoskeleton structure is a typical hallmark of terrestrial vertebrates (tetrapods), preceded earlier in evolution in fish jaw bones and the skeleton of bony fish.…”
Section: Introductionmentioning
confidence: 99%